Urban imaginaries : locating the modern city - Cinar, Alev.; Bender, Thomas (Minneapolis : University of Minnesota Press, 2007)
"For millennia, the city stood out against the landscape, walled and compact. This concept of the city was long accepted as adequate for ch aracterizing the urban experience. However, the nature of the city, bot h real and imagined, has always been more permeable than this model rev eals. The essays in [this book] respond to this condition by focusing o n how social and physical space is conceived as both indefinite and sin gular. They emphasize the ways this space is shared and thus made into urban culture. Urban Imaginaries offers case studies on cities in Brazi l, Israel, Turkey, Lebanon, and India, as well as in the United States and France, and in doing so blends social, cultural, and political appr oaches to better understand the contemporary urban experience."--Publis her description, from p. [4] of cover.
Introduction: The city: experience, imagination, and place / Alev Ci nar and Thomas Bender -- Boundaries, networks, and cities: playing and replaying diasporas and histories / Anthony D. King -- Economy and gend er in the urban borderland: the public culture of Laleli, Istanbul / De niz Yukseker -- Borderlined in the global city (of angels) / Camilla Fo jas -- Modernity on the waterfront: the case of Haussmann's Paris / Mar garet Cohen -- Assembling Douala: imagining forms of urban sociality / AbdouMaliq Simone -- Cities without maps: favelas and the aesthetics of realism / Beatriz Jaguaribe -- Fateful triangles: modernity and its an tinomies in a Mediterranean port city / Mark LeVine -- The imagined com munity as urban reality: the making of Ankara / Alev Cinar -- Urban spa ce, national time, and postcolonial difference: the steel towns of Indi a / Srirupa Roy -- Amman is not a city: Middle Eastern cities in questi on / Seteney Shami -- Let the dead be dead: communal imaginaries and na tional narratives in the post-civil war reconstruction of Beirut / Maha Yahya.
Includes bibliographical references and index.
Keywords: Cities and towns; Cities and towns -- Cross-cultural studies; Sociology, Urban; Social history -- 1970-